Clinical Commentary: Obstetric and Respiratory Management of Pregnancy with Severe Spinal Muscular Atrophy. (16th April 2009) - Flunt, Daniel; Andreadis, Natasha; Menadue, Collette; Welsh, Alec W.
Abstract : We present a combined obstetric and respiratory perspective on two pregnancies for a woman with severe Type 2 Spinal Muscular Atrophy (SMA). Our patient had the lowest prepregnancy weight (20 kg) and vital capacity of 0.34 L (VC 11% predicted) yet to be reported in the sparse literature on pregnancy with SMA. She delivered two live healthy infants via planned caesarean section without pregnancy or neonatal complication. We describe the respiratory and obstetric management techniques used for a pregnancy with this degree of respiratory compromise.